The Difference of Microleakage Between One-Bulkfill Resin Composite and Conventional Resin Composite - Widyapramana Dwi Atmaja; Muhamad Nara Dewanto (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Resin composites are the most commonly used restorative materials and are constantly evolving due to their shortcomings which can affect the restoration results in polymerization shrinkage, leading to the formation of microleakage. Although incremental techniques have been found, this technique has drawbacks regarding the time required and the possibility of contamination. The invention of bulk fill resin composite can solve this problem. Manufacturers of One-Bulkfill (3M ESPE) claim that this material has less polymerization shrinkage than conventional resin composites, which is expected to have less chance of microleakage. This study aims to determine the difference in microleakage between one-bulkfill resin composites and conventional resin composites. 20 extracted premolars without caries and anomalies were utilized as research samples. These teeth were then prepared to form a class 1 cavity, then divided into two groups, namely; (1) One-Bulkfill (3M ESPE) and (2) Z350 XT (3M ESPE). These two samples were immersed in 1% Methylene Blue solution and observed using a Camera with a Macro Lens. Data were analyzed using an independent sample t-test. The results demonstrated a significant difference in microleakage between the two groups (p = 0.014, p0.05). The mean value of microleakage in One-Bukfill composite resin restorations was 0.022, while Z350 XT composite resin restorations had 0.038. It can be concluded that the One-Bulkfill composite resin restoration had a smaller microleakage value than the conventional composite resin restoration (Z350 XT).